Pengaruh Pertanggung Jawaban Sosial Perusahaan (CSR) terhadap Keberlanjutan Usaha Perusahaan (Going Concern) pada PT. TELKOM Div. Regional VII Makassar - Razak, Linda (LP3M Universitas Muhammadiyah Makassar)
This study aimed to test the Influence of Corporate Social Responsibility (Corporate Social Responsibility) Against Business Continuity Company (Going Concern). Sustainability venture company will only be guaranteed if attention to social and environmental dimensions. As this study used descriptive and verification methods are ways of collecting data using questionnaires. The population is taken that employee Social Responsibility Division of PT TELKOM DIV VII REGIONAL Makassar directly related to the company's CSR numbering 25 employees/respondents and the entire population were sampled. The analytical method used is simple regression analysis which is to determine the effect of the Dependent Variables and Variable Independent. Based on the analysis found that the Corporate Social Responsibility (Corporate Social Responsibility) has an influence on Business Continuity Company (Going Concern).